Epiconus syndrome induced only in the erect standing position in a patient with L1 compression fracture: a representative case report. Issue 4 (23rd February 2018) - Kubota, Kenji; Abe, Koki; Orita, Sumihisa; Inage, Kazuhide; Suzuki, Miyako; Sato, Jun; Fujimoto, Kazuki; Shiga, Yasuhiro; Kanamoto, Hirohito; Inoue, Masahiro; Kinoshita, Hideyuki; Norimoto, Masaki; et al.
Key Clinical Message: In daily practice, when CT or MRI does not show a pathological lesion in a patient with persistent abnormal neurological signs, it is important to obtain imaging studies of the spine in dynamic position. Abstract : In daily practice, when CT or MRI does not show a pathological lesion in a patient with persistent abnormal neurological signs, it is important to obtain imaging studies of the spine in dynamic position.